Saberes e práticas dos cirurgiões-dentistas quanto à puericultura odontológica na atenção primária à saúde - Soares, Winnie Vieira (2024)
Childcare monitors child development with an interdisciplinary approach, including oral health care, with an emphasis on preventing cavities, fluorosis and dental trauma. This reinforces the importance of the Dental Surgeon in providing guidance to parents about hygiene and eating habits. The objective of this study was to analyze the performance and knowledge of the Dental Surgeon in childcare activities carried out in the Primary Health Care Units of the Regional Health Coordination V, in the city of Fortaleza. A cross-sectional and descriptive study was carried out, with a quantitative approach, involving 44 dental surgeons from the Regional Health Coordination. Participants responded to a structured questionnaire with sociodemographic data, the performance of dental surgeons and knowledge about dental childcare actions, as established by the City Hall Protocol. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), applying the chi-square test in a bivariate analysis, considering a significance level of 5%. The study was approved by the Research Ethics Committee of the Federal University of Ceará. It was observed that 93.2% of dentists perform childcare, but only 13.6% claim to follow the city hall's protocol, despite 50% knowing the city hall's service protocol. It was found that 40.9% of dentists monitor eight or more children per month and 75% of the first childcare appointments are scheduled through referrals from family health teams. In the first month's consultation, only 34.6% of dentists carried out all the necessary instructions, while in the sixth month's consultation, 50.0% carried them out. However, it was observed that those who knew the childcare protocol were those who better carried out the instructions in the first (p=0.01) and sixth (p=0.04) month consultations. Although 65.9% of participants consider their knowledge of childcare to be good or excellent, it was found that 65.9% still believe that it is important to clean the baby's oral cavity after breastfeeding and 22.7% think that the Fluoride toothpaste should only be used after age 2. The study shows that dentists partially adhere to the Fortaleza protocol, indicating a limited practice of childcare care, highlighting challenges in collaboration with the family health team and in approaching caregivers. Despite there being a large participation in childcare, there are difficulties in scheduling and complying with the protocol. The collaboration is diverse, with challenges linked to the Family Health Strategy, low frequency of ongoing education on the topic and different guidelines for childcare consultations.